Pengaruh Strategi Inovasi terhadap Kinerja Operasional Perusahaan Manufaktur - Rita, Rita (Bina Nusantara University, 2010)
This research examines the effect of innovation strategy towards operational performance of manufacturing companies in Sulawesi. Dimensions of innovation strategy are leadership orientation, process innovation, product innovation, and implementation of innovation. Operational performance is measured by using productivity, volume of production defect, warranty claims cost, quality cost, and full on time delivery to consumers. Data collecting was conducted through questionnares, which consisted of 63 respondents. Data is processed with multiple regressions. Results of this research indicate direct significant effect among the dimensions of innovation strategy to the operational performance of manufacturing companies. But not all of them have an effect on operational performance of the manufacturing company. Process innovation, product innovation, and implementation of innovation give significant effect to the operational performance. Leadership orientation does not give significant effect to the operational performance of the manufacturing companies in Sulawesi.Â